Two Myths about “The Voices”: Experiences of Radio Free Europe/Radio Liberty - Aleknonis, Gintaras (Žurnalistikos tyrimai, 2024)
The article explores the role of international radio broadcasting, with a specific focus on Radio Free Europe/Radio Liberty (RFE/RL), throughout the Cold War era, particularly in Lithuania and the broader Eastern Bloc context. It analyses the influence of these broadcasts, known as “the Voices,” in countering Soviet propaganda and disseminating alternative news to populations living behind the Iron Curtain. The study highlights two crucial aspects, which the author argues attained near-mythical significance: the messengers (i.e., broadcasters) and the content of their messages. Despite Soviet propaganda’s allegations depicting RFE/RL personnel as detached émigrés, as agents of Western intelligence agencies or as former collaborators with Nazis, the text asserts that RFE/RL maintained journalistic autonomy. The Soviet strategy of jamming international broadcasts was complemented by a myth alleging that during the guerrilla struggle for Lithuanian independence at the onset of Soviet occupation, international broadcasters purposefully exacerbated tensions and disseminated unfounded or even false promises of Western assistance. The article rebuts these claims, noting the absence of international broadcasting in Lithuanian during that period. Drawing from recently disclosed documents from the KGB archives, the article demonstrates that despite censorship and efforts to manipulate information, Western broadcasts continued to shape public opinion and reinforce aspirations for independence and democracy in regions under Soviet control.